2020
DOI: 10.3389/fmed.2020.549081
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Isoflurane and Propofol as General Anesthesia During Orthopedic Surgery of Perioperative Cerebral Hypoperfusion Rats to Avoid Cognitive Impairment

Abstract: Background: Perioperative cerebral hypoperfusion (CH) is common, although the underlying mechanism of cognitive impairment that results due to perioperative cerebral hypoperfusion remains to be determined. Isoflurane anesthesia induces neuronal injury via endoplasmic reticulum (ER) stress, whereas a sub-anesthetic dose of propofol improves postoperative cognitive function. However, the effects of the combination of isoflurane plus propofol, which is a common aesthetic combination administered to patients, on E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Previous studies showed that isoflurane minimum alveolar concentration (MAC) value was 1.45 ± 0.17%; 1.9% isoflurane, equivalent to 1.3 MAC, was sufficient to induce general anesthesia in rats (Boruta et al, 2012 ), while a minimal infusion rate at 40 mg·kg −1 ·h −1 was required using propofol alone to induce general anesthesia in rats (Logginidou et al, 2003 ). Our previous study confirmed that a single use of anesthetic dose propofol (40 mg·kg −1 ·h −1 ) or isoflurane (1.9%) aggravated cognitive impairment of aging rats with cerebral hypoperfusion, while a combination of sub-anesthesia dose propofol and isoflurane (1% isoflurane plus 20 mg·kg −1 ·h −1 propofol) did not (Bu et al, 2020 ). However, the effects of different combinations of propofol and isoflurane on hippocampal neurons remain to be explored.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previous studies showed that isoflurane minimum alveolar concentration (MAC) value was 1.45 ± 0.17%; 1.9% isoflurane, equivalent to 1.3 MAC, was sufficient to induce general anesthesia in rats (Boruta et al, 2012 ), while a minimal infusion rate at 40 mg·kg −1 ·h −1 was required using propofol alone to induce general anesthesia in rats (Logginidou et al, 2003 ). Our previous study confirmed that a single use of anesthetic dose propofol (40 mg·kg −1 ·h −1 ) or isoflurane (1.9%) aggravated cognitive impairment of aging rats with cerebral hypoperfusion, while a combination of sub-anesthesia dose propofol and isoflurane (1% isoflurane plus 20 mg·kg −1 ·h −1 propofol) did not (Bu et al, 2020 ). However, the effects of different combinations of propofol and isoflurane on hippocampal neurons remain to be explored.…”
Section: Introductionsupporting
confidence: 77%
“…All this evidences could prove that a single high dose of propofol or isoflurane may cause neuron damage and cognitive impairment, which aroused our interest in studying low-dose combination applications. Our previous in vivo study revealed that combination of sub-anesthetic dose isoflurane and propofol (1% isoflurane plus 20 mg·kg −1 ·h −1 propofol) did not cause cognitive impairment of aged rats with cerebral hypoperfusion as compared with single-use of propofol (20 mg·kg −1 ·h −1 ) or isoflurane (1.9%; Bu et al, 2020 ). In the present study, we compared the effects of three different dosages of isoflurane and propofol (1% and 1.2 μg/ml, 1.4% and 0.6 μg/ml, or 0.5% and 1.8 μg/ml) on primary hypoxic hippocampal neurons with the aim of finding the way to minimize the damage caused by anesthetic to vulnerable neurons.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…All the rats were randomly assigned to the following five groups ( n = 22/group): (1) sham surgery (Sham), (2) CCH, (3) CCH + sub‐anesthetic dose combining propofol and sevoflurane (PS‐low), (4) CCH + PS‐low + BTN (MCE), and (5) CCH + PS‐low + NEM (MCE). The sample size is set based on our previous experience 13,24 . All the outcome assessments were performed by investigators blinded to the group assignments.…”
Section: Methodsmentioning
confidence: 99%
“…•h −1 propofol) did not cause cognitive impairment of aged rats with cerebral hypoperfusion as compared with single-use of propofol (20 mg•kg −1 •h −1 ) or isoflurane (1.9%; Bu et al, 2020). In the present study, we compared the effects of three different dosages of isoflurane and propofol (1% and 1.2 µg/ml, 1.4% and 0.6 µg/ml, or 0.5% and 1.8 µg/ml) on primary hypoxic hippocampal neurons with the aim of finding the way to minimize the damage caused by anesthetic to vulnerable neurons.…”
Section: Discussionmentioning
confidence: 90%